2009
DOI: 10.1152/ajpheart.00167.2009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acute exposure to increased hydrostatic pressure and reduced shear rate on conduit artery endothelial function: a limb-specific response

Abstract: Unlike quadrupeds, humans exhibit a larger hydrostatic pressure in the lower limbs compared with the upper limbs during a major part of the day. It is plausible that repeated episodes of elevated pressure in the legs may negatively impact the endothelium, hence contributing to the greater predisposition of atherosclerosis in the legs. We tested the hypothesis that an acute exposure to increased hydrostatic pressure would induce conduit artery endothelial dysfunction. In protocol 1, to mimic the hemodynamic env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(108 citation statements)
references
References 43 publications
8
99
1
Order By: Relevance
“…The higher incidence of lower extremity lymphedema after inguinofemoral lymph node dissection may be because of anatomic variation, with fewer associated lymphatic collateral pathways, or be related to a specific response to increased hydrostatic pressure in the disrupted lower extremity lymphatics. 55 These findings are concordant with the primary risk factors for lymphedema identified in breast cancer survivors. Specifically, the surgical treatment for breast cancer, which often includes axillary lymph node dissection and/ or mastectomy, is considered a major risk factor for lymphedema 7,56 The extent of lymph node dissection and tumor burden has also been shown to increase the risk of lymphedema.…”
Section: Discussionsupporting
confidence: 77%
“…The higher incidence of lower extremity lymphedema after inguinofemoral lymph node dissection may be because of anatomic variation, with fewer associated lymphatic collateral pathways, or be related to a specific response to increased hydrostatic pressure in the disrupted lower extremity lymphatics. 55 These findings are concordant with the primary risk factors for lymphedema identified in breast cancer survivors. Specifically, the surgical treatment for breast cancer, which often includes axillary lymph node dissection and/ or mastectomy, is considered a major risk factor for lymphedema 7,56 The extent of lymph node dissection and tumor burden has also been shown to increase the risk of lymphedema.…”
Section: Discussionsupporting
confidence: 77%
“…Our findings confirming this suggestion are also supported by the studies investigating increased blood pressure on conduit artery function. In a study, Padilla et al (17) have shown that the brachial artery endothelial vasodilatation was impaired following increase in blood pressure but poplietal artery endothelial function was unaltered. Similar result is found in a study that used the leg press exercise to increase the blood pressure (32).…”
Section: Cardiac Regionmentioning
confidence: 98%
“…The structural and functional alterations of conduit arteries are particularly important in the lower extremities of subjects with cardiovascular disease (15,16). The attenuated endothelium dependent vasodilatation has been found in the upper extremities of subject during acute rise in blood pressure induced by hydrostatic factor (17). Despite the significant work performed on the primary conduit vessels of the arm and leg to assess limb vascular heterogeneity (10)(11)(12)(13)17), only one single work (7) compared upper and lower limb cutaneous vascular function in humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are numerous sitting opportunities throughout the day and the average sitting time for American adults is~8 hr/day [2]. Sitting creates a unique anatomical and physiological milieu in the legs including bends in the femoral and popliteal artery, increased viscosity [3], blood pressure [4] and decrease in arterial shear rates [5]. Interestingly in humans, lower extremities exhibit an increased distribution of atherosclerosis as compared to the upper extremities [6][7][8].…”
Section: Introductionmentioning
confidence: 99%